1996
DOI: 10.1088/0953-4075/29/20/006
|View full text |Cite
|
Sign up to set email alerts
|

Swift cluster-atom collisions: experiment and model calculations

Abstract: Single, double and triple ionization cross sections of 10 MeV projectiles colliding with He atoms have been measured. This was achieved thanks to a new experimental set-up allowing for a complete collection and unambiguous identification (in particular with respect to their charge) of all the fragments emitted by the dissociative species (Q = 2, 3, 4). As a first attempt to understand the mechanisms of ionization in the cluster we use these results, together with those we obtained in the identical velocity 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…The electronic excitation and ionization cross sections exhibit the same evolution with n. This trend is well reproduced by the Independent Atom and Electron (IAE) model 30,36 in the case of ionization. In the IAE calculations, shown by a broken line, classical trajectory Monte Carlo (CTMC) impact parameter probabilities P(b) were used for valence ionization in C and C + as in previous works 25,37 .…”
Section: Iii-1-cross Sections Of Electronic Processessupporting
confidence: 58%
See 1 more Smart Citation
“…The electronic excitation and ionization cross sections exhibit the same evolution with n. This trend is well reproduced by the Independent Atom and Electron (IAE) model 30,36 in the case of ionization. In the IAE calculations, shown by a broken line, classical trajectory Monte Carlo (CTMC) impact parameter probabilities P(b) were used for valence ionization in C and C + as in previous works 25,37 .…”
Section: Iii-1-cross Sections Of Electronic Processessupporting
confidence: 58%
“…In the standard utilization of silicon solid state detectors, the charge delivered by the detector provides the kinetic energy of the fragment i.e its mass for fragments of constant velocity 30 . With this property and the (q/m) analysis, the charge of each fragment was recorded.…”
Section: Ii-4 Detection Of Fragments and Resolution Of The Fragmentat...mentioning
confidence: 99%
“…Díaz-Tendero et al reached the same conclusion by means of DFT and coupled-cluster (CC) theory simulations . Wohrer et al produced both long-lived and excited C 5 2+ ions by high-velocity collisions of 10 MeV C 5 + ions with a He target . They observed that conversely to metal cluster ions, whose dominant fission channels are those giving rise to almost symmetric fragments, the C 5 2+ ions mainly decay to C 4 + + C + .…”
mentioning
confidence: 80%
“…31 Wohrer et al produced both long-lived and excited C 5 2+ ions by high-velocity collisions of 10 MeV C 5 + ions with a He target. 32 They observed that conversely to metal cluster ions, whose dominant fission channels are those giving rise to almost symmetric fragments, the C 5 2+ ions mainly decay to C 4 + + C + . 33 There is also experimental work reporting the detection of the C n 2+ ( n = 2–4) cluster ions using time-of-flight (TOF) mass spectroscopy, 34,35 but the stability and fragmentation dynamics of the clusters have not been explored in detail.…”
mentioning
confidence: 99%
“…Absolute cross sections are derived by integrating over b the IAE probabilities such as (1). Since individual b i 's depend not only on b but also on the grain orientation (Wohrer et al 1994(Wohrer et al , 1996, we average the calculation over all equally probable grain orientations (θ, ϕ in spherical coordinates) following equation ( 4)…”
Section: Model Calculation For Multi-ionizationmentioning
confidence: 99%